Statistics and Analysis of Covid-19 in Ecuador Using Microsoft Power BI - Vivas Paspuel, Atal Kumar (2021)
Given the emergency that Ecuador and the world are going through due to Covid-19, the rapid description and effective analysis of the different variables that explain the evolution of a contagious disease becomes essential. The purpose of this work is to show the versatility that Microsoft Power BI as a business intelligence tool has to describe and analyze the information issued by official health entities that allow generating rapid knowledge and analysis of the data so that it can be taken correct decisions regarding pandemic control. For this, the official information provided by the Ministry of Public Health of Ecuador (MSP) and other news portals was collected. This information was processed and analyzed using the Power BI platform and R software. Analysis of recent data on Covid-19 shows that the disease is still spreading in some localities of the country. The proposal would be to give more and better access to open data and innovate by adding business intelligence to control this pandemic.